2021
DOI: 10.1155/2021/7615712
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-6715-5p Inhibits Cellular Proliferation and Invasion in Colorectal Cancer by Directly Targeting CST4

Abstract: Background. Data on the correlation between CST4 and colorectal cancer (CRC) metastasis are scarce. The aim of this study was to analyze CST4 expression and investigate its biological roles and related microRNA- (miRNA-) mediated regulation in CRC. Methods. The expression of CST4 was examined in cancer tissues and their corresponding adjacent normal tissues from 40 gastric adenocarcinoma patients. The expression level of CST4 in specimens (cancer and normal tissues) was assessed through immunohistochemistry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…CSTs have also been suggested as a prognostic biomarker for various cancers [57][58][59]. CST4, known as cystatin SA, was also founded highly expressed in gastric and colorectal cancer to promote cell proliferation, invasion, and metastasis [42,60]. The role of CST4 in breast cancer, particularly in TNB [61]C, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CSTs have also been suggested as a prognostic biomarker for various cancers [57][58][59]. CST4, known as cystatin SA, was also founded highly expressed in gastric and colorectal cancer to promote cell proliferation, invasion, and metastasis [42,60]. The role of CST4 in breast cancer, particularly in TNB [61]C, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CYS2 may help regulate the TGF-β signaling pathway and promote EMT like CYS1, but the mechanism needs further exploration to be certain [131]. CST4 is upregulated in esophageal, colon, and gastric cancer and is associated with poor prognosis [133][134][135]. The overexpression of CYSS in gastric tumor cells upregulates a protein called ELFN2, which directly inhibits the expression of E-cadherin and promotes EMT, like CYS1 and CYS2 [134].…”
Section: Other Sd-type Cystatins (Cst2 Cst4 Cst5)mentioning
confidence: 99%
“…MiRNA is a kind of small non-coding RNA transcript consisting of 19–25 bases ( Goldberger et al, 2013 ; Berindan-Neagoe et al., 2014 ; Boissinot et al, 2020 ); it plays key roles in many physiopathological processes, such as energy metabolism, tumorigenesis, and immune response ( Lenart et al, 2020 ; Gangaraju & Lin, 2009 ; Taniguchi, Uchiyama & Akao, 2021 ). Mounting studies have revealed that a lot of miRNAs are dysregulated in CRC ( Shi, Zhou & Zhang, 2021a ; Lan et al, 2021 ; Zhang et al, 2021 ), prostate cancer ( Coarfa et al, 2016 ), and breast cancer ( Lorenzo-Martin et al., 2019 ), etc. MiRNAs post-transcriptionally regulate gene expression by binding to the 3′ untranslated region (3′ UTR) of target mRNAs, making possible to function as oncogenes, tumor suppressors, or drug resistance factors in different cases ( Shi, Zhou & Zhang, 2021a ; Lan et al, 2021 ; Zhang et al, 2021 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mounting studies have revealed that a lot of miRNAs are dysregulated in CRC ( Shi, Zhou & Zhang, 2021a ; Lan et al, 2021 ; Zhang et al, 2021 ), prostate cancer ( Coarfa et al, 2016 ), and breast cancer ( Lorenzo-Martin et al., 2019 ), etc. MiRNAs post-transcriptionally regulate gene expression by binding to the 3′ untranslated region (3′ UTR) of target mRNAs, making possible to function as oncogenes, tumor suppressors, or drug resistance factors in different cases ( Shi, Zhou & Zhang, 2021a ; Lan et al, 2021 ; Zhang et al, 2021 ; Wang et al, 2021 ). Dysregulated expression of miRNAs is correlated with cancer cell proliferation, migration, and invasion ( Zhang et al, 2021 ; Li et al, 2015 ; Duan et al, 2017 ; Lan et al, 2021 ; Ding et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%